Peluang Dan Ancaman Perdagangan Bebas Studi Kasus Indonesia – Malaysia Untuk Komoditas Pertanian Pada Biji Kopi - Aprilia Putri; Nahayotul Novus; Rina Latifah Utami; Muhammad Rifqy Fauzan (Jurnal Ekonomi dan Bisnis Digital, 2024)
International trade between Indonesia and Malaysia in the coffee sector has great potential for economic growth in both countries. Even though Indonesia is one of the largest coffee producers in the world and Malaysia is the main market for Indonesian coffee, challenges such as competition with other countries, global price fluctuations and dumping practices need to be addressed to ensure the continuation of fair trade. Balanced and sustainable. Free trade between the two countries opens up opportunities for product diversification, increased market access, and strengthened cooperation, but differences in trade regulations, export-import policies, as well as price and quality competition need to be taken into account. Economic cooperation in the ASEAN Free Trade Area (AFTA) also has a significant impact on Indonesian coffee exports to Malaysia. By paying attention to these factors, trade cooperation between Indonesia and Malaysia in the coffee sector can become the basis for sustainable and mutually beneficial economic growth for both countries.